2022
DOI: 10.1590/fst.18121
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of spray-drying conditions for obtaining Bacillus sp. SMIA-2 protease powder

Abstract: Microbial proteases, especially from Bacillus spp., have enormously been exploited for a broad variety of applications such as for physiological processes, food and feedstuff, detergents, as well as in the pharmaceutical and leather. In this work, proteases produced by the thermophilic Bacillus sp. SMIA-2 submerged cultures were spray-dried in an attempt to improve its stability for applications in industry. The enzymatic extract was dried using drying adjuvants, and optimal conditions for preserving enzymatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Moreover, the addition of NaCl at 0.1% (v/v) in the medium containing 15 g/L of wheat bran significantly improved proteases, amylases, and endoglucanases co-production by 1.22 folds, 1.23 folds, and 1.6 folds, respectively ( Table 2 ). Previous studies [ [42] , [43] , [44] ] have reported that NaCl enhances enzyme secretion. Indeed, this salt exhibits a crucial role in protecting and stabilizing proteins from inactivation [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the addition of NaCl at 0.1% (v/v) in the medium containing 15 g/L of wheat bran significantly improved proteases, amylases, and endoglucanases co-production by 1.22 folds, 1.23 folds, and 1.6 folds, respectively ( Table 2 ). Previous studies [ [42] , [43] , [44] ] have reported that NaCl enhances enzyme secretion. Indeed, this salt exhibits a crucial role in protecting and stabilizing proteins from inactivation [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Between the excipients evaluated, maltodextrin gave the best effects. Similarly, Naganthran et al showed the important role of maltodextrin in the stability of protease, amylase, and lipase [ 44 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation